Upaya Membangun Ketahanan Keluarga pada Pasangan Suami Istri yang Mengalami Infertilitas - Sholikhah, Nazun Mar'atu; Ruhaena, Lisnawati (Personifikasi: Jurnal Ilmu Psikologi, 2024)
Infertility is a physical health problem of the reproductive system that makes it difficult for husbands and/or spouses to have children. Infertility in married couples might have an impact on family resilience. The purpose of this study is to explain methods to strengthen family resilience in infertile married couples. Non-random purposive sampling was used to select 8 informants (4 couples). This is a qualitative study utilizing a descriptive methodology. Semi-structured interviews and documentation were used to obtain data. Interactive models are used to analyze data. The findings of this study indicate that infertility has an effect on the psychological state of married couples, such as feelings of loneliness, sadness, jealousy, inferiority, and so on. Internal and environmental factors influence family resilience in married couples enduring infertility. Efforts made to build family resilience include thinking positively, not exaggerating problems, not demanding or blaming each other, being optimistic about having children, accepting each other's shortcomings and strengths, always communicating openly, trusting each other, supporting each other, helping each other, caring for each other, loving each other, understanding each other, filling each other's emptiness, always being together, strengthening each other, always being loyal to one's partner, living happily, surrendering to God, being grateful for all circumstances, and doing activities that one enjoys. The practical consequences of this study for married couples battling infertility are the ability to recover from challenging circumstances, as well as the ability to find and make efforts to develop a family.